Emotional Intelligence and Student Interest to Follow Professional Accounting Education - Teguh Erawati; Rina Iriyanti (Universitas Muhammadiyah Makassar, 2023)
Emotional intelligence, attitude, quality motivation, career motivation, and economic motivation all play a role in accounting students' interest in taking the Accounting Profession Education (APE) program, according to this study (PPAk). This is a survey study using a causal comparative quantitative method. this type of study. Among the characteristics being studied are accounting students' interest in the Accounting Profession Education, as well as their emotional intelligence, attitude, and quality motivation (PPAk). At the Faculty of Economics, the University of Sarjanawiyata Tamansisw, students who have undergone auditing courses are included in the population. Convenience Sampling Method of Sampling. Questionnaires will be used to gather data for this project. With a 5% level of significance, multiple linear regression is utilized in the study. The results in this study indicate that emotional intelligence, attitude, quality motivation, career motivation, and economic motivation partially have a positive and significant effect on the interest of accounting students to take the Accounting Profession Education (PPAk). Simultaneously emotional intelligence, attitude, quality motivation, career motivation, and economic motivation have a positive and significant effect on the interest of accounting students to take the Accounting Profession Education (PPAk).